(untitled) (Socio-Economic Development Panorama, 2009)
Recent studies have shown that young child labourers depressed state of school enrollment rates, negatively affect school achievement, and decreases graduation rates. Given these realities, recent cash transfer programmes have a comprehensive social protection approaches that encourage schooling by providing beneficiary compliance with requirement to schooling, vaccine, or other health-related conditions. These cash-transfer programmes have tried to dismantle the intergenerational poverty cycle, and thus have improved school attendance while reducing the number of child labourers. In educating its young children, India remains so far behind the rest of Asia, that it will take a major infusion of resources, and political leadership to catch up. This paper draws the attention of the educational policy makers and development agencies to reveal the nexus between compulsory primary education, and the issue of child labourers in India. Key words: Compulsory education, government and education, universalization of education, education system, children and education Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June